Expression of amino acid transporters (LAT1, ASCT2 and xCT) as clinical significance in hepatocellular carcinoma. Issue 9 (11th December 2014) - Namikawa, Masashi; Kakizaki, Satoru; Kaira, Kyoichi; Tojima, Hiroki; Yamazaki, Yuichi; Horiguchi, Norio; Sato, Ken; Oriuchi, Noboru; Tominaga, Hideyuki; Sunose, Yutaka; Nagamori, Shushi; Kanai, Yoshikatsu; et al.
<x xml:space="preserve">Abstract</x> Aim Amino acid transporters play an important role in tumor progression and survival of cancer cells. However, the prognostic significance of L‐type amino acid transporter 1 (LAT1), system ASC amino acid transporter‐2 (ASCT2) and xCT expression in patients with hepatocellular carcinoma (HCC) remains unclear. The aim of this study is to investigate the clinicopathological significance of these amino acid transporters in patients with HCC. Methods We examined 84 patients with surgically resected HCC. Tumor sections were stained by immunohistochemistry for LAT1, ASCT2, xCT, 4F2hc/CD98hc (4F2hc), Ki‐67 and microvessel density (MVD) determined by CD34. Results LAT1, 4F2hc, ASCT2 and xCT were positively expressed in 61% (50/84), 77% (65/84), 63% (53/84) and 65% (55/84), respectively. Positive LAT1 expression was significantly associated with 4F2hc expression, Ki‐67 and the serum albumin. By univariate analysis, LAT1 expression, disease stage and albumin had a significant relationship with overall survival. Tumor size, disease stage, portal vein invasion, albumin and α‐fetoprotein had a significant relationship with progression‐free survival. Multivariate analysis confirmed that LAT1 expression is an independent and significant prognostic factor for predicting worse outcome after surgery. Conclusion LAT1 can serve as a significant prognostic marker for predicting negative prognosis after surgery.